Bilateral supernumerary kidneys: how much is too much?. (1st April 2014) - Patel, Ruchir; Singh, Hanish; Willens, David; Drake, Sean
Abstract : A middle aged African-American woman with a stable history of carnitine palmitoyl transferase II (CPT II) deficiency presented with myalgias for 1 week. Physical examination and laboratory findings were consistent with severe sepsis secondary to pyelonephritis leading to rhabdomyolysis. Subsequent CT of the abdomen revealed bilateral supernumerary kidneys with non-obstructive calculi within the supernumerary kidneys. Abnormal ureteral development of the supernumerary kidneys likely led to an increased risk for urinary tract infections (UTIs) and renal calculi resulting in pyelonephritis. The stress of this infection overwhelmed the muscle CPT II enzyme load, putting her in a state of rhabdomyolysis. In addition to fluids and antibiotics, she was provided a diet rich in carbohydrates and low in fats so as to limit long-chain fatty acid oxidation. Supernumerary nephrectomy was not considered during this admission. During follow-up, she developed obstructive ureteral calculi requiring placement of a right-sided ureteral stent.